Cell signaling - is it new?. - Geddes, L.A.
In these days of tissue engineering the term "cell signaling" is encountered frequently, and it refers to an effect that one type of cell produces on an adjacent or distant but different cell types. In most cases the effect is mediated by a chemical messenger. The discovery of chemical messengers originated with Bayliss and Starling (1902) who were interested in digestion in the gastrointestinal tract, and with Loewi (1923) whose interest focused on the heart. These classical experiments are described here. The two investigations clearly demonstrated the ingenuity of the investigators to design simple but elegant experiments that demonstrated cell signaling and gave rise to the whole field of endocrinology, which deals with hormones, the definition of which is a discrete chemical substance secreted into the body fluids by an endocrine gland, which has a specific effect on the activities of other organs.
Keywords: Body fluids; Cell signaling; Chemical messenger; Classical experiments; Digestion; Discrete chemical substance; Endocrine gland; Endocrinology; Gastrointestinal tract; Heart; Hormones; Organs; Tissue engineering